Treatment of Mycobacterium haemophilum infection in a murine model with clarithromycin, rifabutin, and ciprofloxacin. - Atkinson, B A (1995)
An animal model of disseminated Mycobacterium haemophilum infection was utilized to compare treatment with azithromycin, ciprofloxacin, rifabutin, and the combination of clarithromycin with rifabutin. Following subcutaneous challenge with M. haemophilum, local and disseminated infection occurred only in immunosuppressed mice. For disseminated infection, ciprofloxacin was relatively ineffective therapy. Clarithromycin and rifabutin alone significantly reduced the tissue burden in the spleen after 4 weeks of therapy. Combination therapy with rifabutin and clarithromycin was superior to 4 weeks of treatment with the individual agents. When immunosuppressed mice were treated for 20 weeks with the combination of rifabutin and clarithromycin, the tissue burden remained reduced in the spleen at 1 month following the completion of therapy. Combined rifabutin and clarithromycin provide effective treatment for M. haemophilum in this model.